Acute hemorrhagic cholecystitis related to diffuse neurofibroma of gallbladder in a patient with neurofibromatosis type 1 - Takeshi Omura; Koichi Ikawa; Eiji Kudo (Surgical Case Reports)
Abstract Background We report the first case of acute hemorrhagic cholecystitis with large hemoperitoneum related to gallbladder wall fragility caused by neurofibroma cell infiltration. Case presentation A 46-year-old man with neurofibromatosis type 1 (NF1), who had been hospitalized for retroperitoneal hematoma and treated by transarterial embolization 9 days earlier, complained of right upper quadrant pain, bloating, nausea, and emesis. Computed tomography revealed fluid collection and a distended gallbladder with high-density contents. The patient was taken to the operating room for laparoscopic cholecystectomy, with consideration of the hemodynamic tolerance, for acute hemorrhagic cholecystitis. An initial laparoscopy revealed a significant amount of blood in the abdominal cavity exuding from the gallbladder. Due to its fragility, the gallbladder was easily ruptured by surgical manipulation. After conversion to open surgery, subtotal cholecystectomy was performed. Seventeen days after surgery, the patient was transferred to another hospital for rehabilitation. Histological examination revealed diffuse and nodular proliferation of spindle cells that had replaced the muscularis propria of the gallbladder wall. Conclusion This clinical case highlights how NF1 can cause various symptoms in the blood vessels and gastrointestinal tract, including the gallbladder.